Acesso a exames de pré-natal no Brasil: resultados da Pesquisa Nacional de Saúde 2013 e 2019 - FREITAS, Francisca Maria da Silva (2024)
Introduction: Laboratory tests/exams are a fundamental part of prenatal care and aim to prevent, diagnose, and treat diseases or deficiencies, ensuring better health outcomes during pregnancy and birth. Brazil has high prenatal care coverage offered by a network of public and private services. However, prenatal testing is still not homogeneous between population groups and localities in the country. Objectives: To analyze the prevalence of prenatal exams for pregnant women and the factors associated with the variation in this prevalence, between the years of the National Health Survey 2013 and 2019. Method: Cross-sectional study with dates pregnant women aged 18 to 49 years that received prenatal care and were interviewed in the PNS conducted in 2013 (n=1,851) and 2019 (n=2,729). Four tests/exams were examined: blood, urine, syphilis, and HIV. The prevalence and respective 95% confidence intervals (95%CI) of the individual and combined tests/exams were estimated for each year of the National Health Survey. Additionally, the absolute difference and the 95%CI of the change in prevalence over the period were estimated. Poisson regression models, with robust variance, were tested for the association between the year of the PNS (2019 vs 2013) with the access to all prenatal tests. Results: The proportion of pregnant women who reported having had prenatal care in Brazil was 97.3% (95% CI: 96.4; 98.3) in 2013 and 98.2% (95% CI: 97.5; 98.8) in 2019. The most prevalent were urine and blood tests, and the least prevalent were syphilis and HIV. During the period, the number of tests for syphilis (15.2; 95% CI: 11.0; 22.0) and HIV (4.3; 95% CI: 4.3; 8.0) increased, but the number of the others decreased. The prevalence of all four tests increased (9.9; 95%CI: 5.0; 16.0), reaching 69.9% (95%CI: 67.0; 72.8) in 2019 compared to 60.0% (95%CI: 56.1; 63.9) in 2013. This growth occurred in the country's most vulnerable groups and localities. In the period, the adjusted regression analysis indicated a greater chance of access to all four tests (PR=1.16; 95%CI: 1.10; 1.16), syphilis (PR=1.21; 95%CI: 1.15; 1.27), and HIV (PR=1.04; 95%CI: 1.03; 1.06). Nonetheless, it reduced the chance of access to blood (PR=0.97; 95%CI: 0.96; 0.98) and urine tests (PR=0.95; 95%CI: 0.94; 0.96). Conclusion: The results showed greater completion of the set of four prenatal tests/examinations, and specifically, two of them: syphilis and HIV. The advance in all tests/examinations was for the most vulnerable groups and locations in the country. However, this prevalence was still low and it was associated with vulnerable groups and locations, indicating the persistence of inequalities in Brazil. Therefore, more vulnerable pregnant women still face difficulties in accessing routine prenatal exams recommended in maternal and child health care.